Pengaruh Penggunaan Edpuzzle Terhadap Hasil Belajar Siswa Pada Materi Kearifan Lokal Di Kelas III - Saputra, Ritho Apriyandi (JPPSD: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2026)
This study aims to analyze the effect of using Edpuzzle interactive video media on student learning outcomes on local wisdom material in third grade elementary schools. The study used a quantitative approach with a quasi-experimental design of the nonequivalent control group design. The subjects were all 43 third grade students of SDN 80/I Muara Bulian, consisting of the experimental class and the control class. The data collection technique used objective tests in the form of pretests and posttests. Data analysis was carried out through prerequisite tests and hypothesis testing using t-tests. The results showed that there were significant differences in learning outcomes between students who learned using Edpuzzle and students who learned using conventional methods. This finding indicates that the use of Edpuzzle is effective in improving student learning outcomes on local wisdom material. This study provides implications that the use of interactive digital media based on local culture can be an alternative innovative learning strategy in elementary schools.